2014
DOI: 10.4239/wjd.v5.i3.372
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and cancer: Associations, mechanisms, and implications for medical practice

Abstract: Both diabetes mellitus and cancer are prevalent diseases worldwide. It is evident that there is a substantial increase in cancer incidence in diabetic patients. Epidemiologic studies have indicated that diabetic patients are at significantly higher risk of common cancers including pancreatic, liver, breast, colorectal, urinary tract, gastric and female reproductive cancers. Mortality due to cancer is moderately increased among patients with diabetes compared with those without. There is increasing evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
107
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 98 publications
1
107
0
Order By: Relevance
“…In addition, exposure to a wide range of toxins as well as type 2 diabetes (T2D) and obesity have been suggested as important mediators of the complex process of myelomagenesis (Alexander et al 2007, Lope et al 2008, Wallin & Larsson 2011. Among these latter preventable factors, T2D has attracted significant attention since it has been consistently identified as a medical condition frequently found in MM patients (Khan et al 2008, Richardson et al 2009, Castillo et al 2012 and it is thought to influence the myelomagenesis through hyperglycaemia and insulin-dependent and -independent mechanisms (Xu et al 2014). In a recent well-powered meta-analysis, Castillo et al (2012) observed that T2D was significantly associated with an increased risk of developing the disease (Castillo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, exposure to a wide range of toxins as well as type 2 diabetes (T2D) and obesity have been suggested as important mediators of the complex process of myelomagenesis (Alexander et al 2007, Lope et al 2008, Wallin & Larsson 2011. Among these latter preventable factors, T2D has attracted significant attention since it has been consistently identified as a medical condition frequently found in MM patients (Khan et al 2008, Richardson et al 2009, Castillo et al 2012 and it is thought to influence the myelomagenesis through hyperglycaemia and insulin-dependent and -independent mechanisms (Xu et al 2014). In a recent well-powered meta-analysis, Castillo et al (2012) observed that T2D was significantly associated with an increased risk of developing the disease (Castillo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that T2D and MM have strong genetic components and share several biological pathways and markers (Xu et al 2014) and that T2D-related polymorphisms may influence the risk of developing solid cancer (Folsom et al 2008, Cheng et al 2011, we hypothesized that genetic risk factors for T2D may be associated with the risk of developing MM. So far there have not been studies evaluating the impact of diabetogenic variants on the risk of developing hematological cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiologic findings indicate that diabetic patients are at significantly higher risk for cancer development. On the other hand, DM is a more common problem in patients with advanced cancer than in normal population 11 .…”
Section: Resultsmentioning
confidence: 99%
“…With regards to diabetes, it appears that there is no requirement for changes in clinical practice in terms of anti-diabetic medications. By contrast, there remains the requirement for improved quantifying sub-optimal treatments and outcomes among patients with diabetes that develop cancer (30). Other factors, such as how to optimally adjust chemotherapy doses for increasingly obese patients, have received less attention (31).…”
Section: Resultsmentioning
confidence: 99%